Perancangan Website dengan Menerapkan Customer Relationship Management (CRM) - Riko Dwi Putra; Muhammad Adam Husin (Majalah Ilmiah UPI YPTK, 2021)
With the technology that is currently developing, especially in the online sales business, an online sales website is designed on the Wishy Store Distro by designing customer relationship management in attracting customer shopping interest in the products sold by providing and supporting the best service to customers. . The customer relationship management features that are presented and designed include, among others, customers can get a discount for a certain amount of purchase, customers can get free shipping for a certain number of purchases, customers can contact the Wishy Store Distro admin to ask about products for returns for shipping errors or defects. products, customers can create and send statuses about products being sold and can give likes to fellow customers or other users who have posted statuses on the feed page. The design of Customer Relationship Management on the Wishy Store Distro uses PHP as the programming language with MySQL as the database, Sublime Text 3 and Notepad ++ as the script editor.